Lipid metabolism reprogramming in chronic obstructive pulmonary disease - Qianqian Liang; Yide Wang; Zheng Li (Molecular Medicine)
Abstract Chronic Obstructive Pulmonary Disease (COPD) is a complex and diverse respiratory disorder, characterized by ongoing respiratory symptoms and restricted airflow. The major clinical manifestations typically encompass chronic cough, sputum production, and wheezing. The main pathological characteristics involve infiltration of inflammatory cells, overproduction of mucus, and damage to the alveolar walls. The underlying causes of COPD are complex and remain incompletely elucidated, thought to originate from the combined effect of various factors. Lipids, as hydrophobic molecules, fulfill three fundamental functions: energy storage, membrane biosynthesis, and signal transduction. Lipid metabolism is intricately intertwined with various metabolic pathways and plays a pivotal role in the complex pathogenesis of COPD. Delving into lipid metabolism, as well as the particular modifications and roles of lipid molecules in cells, is of paramount importance in the context of COPD. This review primarily aims to elucidate the role of fatty acid metabolism in the onset and progression of COPD. Additionally, it examines the potential of lipid metabolism reprogramming as a promising therapeutic approach, illuminating new paths for the management and treatment of this disabling respiratory condition.